SME Instrument: an empirical analysis on the impact of the second phase on the performance of Italian enterprises - Peppino De Rose; Daria Malavenda (European Scientific Journal, ESJ, 2024)
This article is part of the strand of research on evaluating the effectiveness of public funds in stimulating the growth of research and development activities in the private sector. The research focus is on the SME Instrument, in its original version born within Horizon 2020, and in particular Phase 2 of the instrument. The research question, therefore, is "Has the second phase of the SME Instrument had a positive impact on the Italian SMEs that have joined it? If yes, to what extent?" The evaluation will be based on quantitative data inherent in the innovation (and non-innovation) performance of individual firms. At the conclusion of the analysis, it can be concluded that the second phase of the SME Instrument did not produce significant additional effects on the performance of firms, approximated by the ratio of total sales to total assets. The only exception is for those enterprises aged between 6 and 15 years, for which there is a partially significant increase in the sales/assets ratio after receiving funding. Given the research results and given that public and private management share a common interest in making their investments effective and efficient by seeing a return on them, the implications for policymakers are twofold: personalization of policy and promotion of an integrated innovation model, both of which imply a rethinking of the instrument. However, like any research, the results obtained are never an end-point, but the starting point for new reflections from which to develop further research.